Illustrated russian grammar - Snetkov, Goutta (RLT Books, 2016)
Illustrated Russian Grammar: Covers all the key points of elementary Russian grammar. Infographics and illustrations in the book produce visually engaging explanations. Practice exercises. Comprehensive table of regular and irregular Russian verbs. Can be used for self-study or as a supplement to any textbook.